PRODUÇÃO DE BIOMASSA E QUANTIFICAÇÃO DE NUTRIENTES EM Eucalyptus benthamii Maiden et Cambage SOB DIFERENTES DENSIDADES DE PLANTIO - Silva, Saulo Vinicius Küster da (2015)
This study aimed to evaluate the production of aboveground biomass, the content and the allocation of nutrients in Eucalyptus benthamii trees, under four different planting densities, at six years of age. Thus, it was placed experimental planting design in randomized blocks, with the planting spacing 3x2, 3x3, 4x3 and 4x4, with four replications composed of 20 trees each. Trees were selected in all diameter classes to determine the height, total biomass and wood compartments, bark, branches and leaves. Subsequently, samples were taken to obtain the dry weight in each compartment. To determine the nutrient content in different compartments of the trees, samples were used from the median tree of the five most frequent class in each treatment. The higher total dry matter was found in treatment 1, which corresponds to the spacing 3x2 with 184.2 Mg ha?¹, followed by treatments 2 (3x3), 3 (4x3) and 4 (4x4) with 147.3 , 133.5 and 109.3 Mg ha?¹. On average, the timber contributed 75.2% of the total biomass, followed by peeling to 13.1%, with 7.4% of the branches and leaves to 4.3%. However, the biomass of wood and bark had a tendency to decrease its contribution to total biomass as spacing increases. The reverse happens with compartments branches and leaves, due to the wider spacing that allows further development of the treetops. The treatments did not significantly interfere in the concentration of macronutrients and micronutrients in any of the compartments. It was found the following descending order in concentration of macronutrients: Ca> N> K> Mg> S> P. As for micronutrients, the order was: Mn> Fe> Zn> Cu> B. With regard to the content stored by the total biomass above soil, the macronutrients were presented in descending order: N> Ca> K> P> Mg> S and distributed in this way by compartments: wood> bark> leaves> branches. For micronutrients, the descending order was: Mn> Fe> Zn> Cu> B, with the following order of distribution by compartments: bark> wood> leaves> branches.